(untitled) (Indian Journal of Child Health, 2022)
Galactosialidosis is a rare autosomal recessive lysosomal storage disorder (LSD). It results from defects in glycoprotein degradation due to mutation in a single gene, encoded by the protective protein cathepsin A, (CTSA), located on chromosome 20q13.12. Most cases of non-immune hydrops fetalis (NIHF) nowadays being recognized are due to cardiac, lymphatic dysplasia, and hematological disorders. Inborn errors of metabolism account for NIHF in 1.3% of patients. Among metabolic disorders, around 14 LSDs have been reported as being associated with NIHF and congenital ascites. In the present case, we report an early infantile form of galactosialidosis with a novel homozygous miss-sense mutation c.319 A>C (p. Ser107 Arg) in exon 3 of CTSA gene in a newborn who presented as non-immune hydrops. The baby also had coarse facies, wide anterior fontanelle, hypertelorism, bilateral congenital talipes equinovarus, hepatosplenomegaly, nephrocalcinosis, and disproportionately small limbs with metaphyseal irregularity. Gradually, he developed worsening cardiac functions and cardiomyopathy and succumbed to death on day 47 of life. Being an autosomal recessive disorder, it can recur in the next pregnancy and treatment is mainly supportive. Targeted prenatal diagnostics in subsequent pregnancies can help in early diagnosis.